NURSING CARE TO NY.K's CLIENT WITH COMPLICATIONS OF DIABETIC ULCUS IN THE INTERNAL OF FL TOBING HOSPITAL, SIBOLGA IN YEAR 2021 - Pius Kosmas Fau; Rumiris Simatupang; Mita Simanjuntak (Institute of Computer Science (IOCS), 2022)
Diabetic ulcers as a chronic complication of Diabetes Mellitus,where as many as 56% of cases of diabetic ulcers accompanied by infection will experience diabetic foot ulcers and will develop into tissue death, if not treated intensively can lead to amputation diabetic ulcer.The results of the case report found data on Mrs. N,namely the client said about ± 1 month the wound did not heal.The wound was located on the left lower extremity.The client says the wound smells, the client's wound looks red, swollen, wet and has pus, the wound is covered with a bandage.The condition of the bandage looks wet and there is blood,on the client's wound there is a lot of necrotic tissue on the edges and surface of the wound, the wound on the big toe of the left p: ±5cm L: ±6 cm and the wound on the back of the foot with a diameter of 6 cm.Pain in the leg with the wound, the pain feels like being stabbed-stab.Pain scale 4,occurs during activity and decreases at rest.The client looks tense when the wound on his leg is cleaned, and the client grimaces when the ulcer is pressed.The client said that while in the hospital his sleep was not comfortable.The results of the study found problems in Ny.N, namely damage to tissue integrity and pain.Based on the nursing problems above,a plan is drawn up and carries out nursing actions and evaluations that refer to the goals and outcome criteria.To prevent the increase of Diabetic Ulcers,it is recommended to hospital agencies to carry out intensive care and provide adequate information to patients about Diabetic Ulcers themselves.